Biological carbon pump efficiency in the Humboldt current system off Peru: flux coefficients - Engel, Anja (In: Engel, Anja; Cisternas-Novoa, Carolina; Hauss, Helena; Kiko, Rainer; Le Moigne, Frédéric A C (2023): Biological carbon pump efficiency in the Humboldt current system off Peru: sediment traps during METEOR cruises M136 and M138 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963289, 2023)
Potential drivers of export flux attenuation: relationship between carbon export flux and satellite-derived primary production28 (PP, during period of deployment), export flux attenuation coefficient (Martin-b) and biochemical parameters indicative of particle quality as obtained in the deepest trap of each deployment. The particle interceptor traps were deployed six times (T1, T2, T3, T4, T6, T7) at different locations off Peru (12.0°S-14.6°S and 77.3°W-78.6°W) during the RV METEOR cruises M136 and M138 at four times in April and two times in June 2017.